An Assessment of the Intrinsic Worth of Pankaj Mishra's The Romantics. - Joshi, Madhu (Poetcrit, 2007)
The article presents a critical analysis of the intrinsic worth of Pankaj Mishra's novel "The Romantics." The novel focuses attention on the ancient and the modern worlds, as also the Indian and the Western. A discussion of the portrayal of the relationship between two major characters in the book is provided. It highlights commentaries on the work of Indian writers in English, including Mishra.